A Lightweight and Secure Anonymous User Authentication Protocol for Wireless Body Area Networks. (22nd July 2021) - Zhang, Junsong; Zhang, Qikun; Li, Zhigang; Lu, Xianling; Gan, Yong
Abstract : The recent development of wireless body area network (WBAN) technology plays a significant role in the modern healthcare system for patient health monitoring. However, owing to the open nature of the wireless channel and the sensitivity of the transmitted messages, the data security and privacy threats in WBAN have been widely discussed and must be solved. In recent years, many authentication protocols had been proposed to provide security and privacy protection in WBANs. However, many of these schemes are not computationally efficient in the authentication process. Inspired by these studies, a lightweight and secure anonymous authentication protocol is presented to provide data security and privacy for WBANs. The proposed scheme adopts a random value and hash function to provide user anonymity. Besides, the proposed protocol can provide user authentication without a trusted third party, which makes the proposed scheme have no computational bottleneck in terms of architecture. Finally, the security and performance analyses demonstrate that the proposed scheme can meet security requirements with low computational and communication costs.